Effects of High Ambient Temperature on Small Intestinal Morphology and Colonic Microbiota in Weaned Piglets - Shuaibing Xing; Shuai Chen; Ying Zhao; Yuheng Luo; Bing Yu; Jun He; Zhiqing Huang; Ping Zheng; Xiangbing Mao; Junqiu Luo; Hui Yan; Jie Yu (Animals, 2022)
A total of 16 crossbred (Duroc × Landrace × Yorkshire) barrows, with an average initial body weight of 8.61 ± 0.24 kg (28 days of age), were randomly allotted into the control group (CON group) and high ambient temperature group (HT group) with 8 replicates per group, 1 pig per replicate. The ambient temperature of the CON group was controlled at 26 ± 1 °C, and the HT group was controlled at 35 ± 1 °C. The study lasted for 21 days. Our results showed that high ambient temperature significantly decreased the average daily feed intake (ADFI) and average daily gain (ADG) of piglets (p < 0.05), and the feed-to-gain ratio was significantly increased (p < 0.05). The liver index, spleen index, and thymus index of piglets in the HT group were significantly decreased (p < 0.05). The villous height (VH) of the duodenum, jejunum, and ileum of piglets in the HT group was significantly decreased (p < 0.05), whereas the crypt depth (CD) of the duodenum was significantly increased (p < 0.05), and the VH-to-CD ratio of the duodenum and ileum was significantly decreased (p < 0.05). The piglets in the HT group showed a higher (p < 0.05) observed-species index, PD whole tree index, and Shannon index, indicating that there was a significant difference in species richness and diversity between the two groups. At the genus level, the piglets in the HT group showed a greater (p < 0.05) percent of Desulfovibrio, Occillibater, and Catenisphaera. HT reduced glycan biosynthesis and metabolism, transport and catabolism, lipid metabolism, amino acids metabolism, secondary metabolites biosynthesis, aging, endocrine system, signaling molecules, and interaction of colon microbiota (p < 0.05), and increased signal transduction, cell motility, transcription, and genetic information processing (p < 0.05).